Bijolia Temple Complex - Temples of India Project Team (Jio Institute, 2024)
The Bijolia Temple complex is comprised of three temples which are known as Hazareshwar, Undeshwar and Undeshwar temple. In the temple complex, a kund is also situated which is known as Mandakini Kund. In the given image Mahakal Temple and Hazareshwar can be seen.